Cultivating an Attitude of Professionalism Based on Prophetic Value - Yeni Rosilawati; Faisal Muhammad Amanullah (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2021)
Professionalism is a matter of attitude towards the values ​​that apply in the world of work. Professionalism is a condition or attitude manifested by individuals in carrying out their duties. In its implementation, it requires individual expertise as a result of learning from specific education or training. However, in today's reality, the Indonesian people have not put forward the values ​​of professionalism in every work activity. So what happens is that various cases such as corruption and fraud occur. This study aims to analyze the attitude of professionalism and its relationship with prophetic values. This study uses qualitative research methods with data collection techniques through literature study. Qualitative research is a way of analysis to understand the meaning behind individuals or groups in personal or social problems. The research data were taken from various books, journals, and news articles to provide data on professional attitudes and prophetic values. The researcher analyses and interprets the collected data as a reference and answer to the existing problems. The results show that in Islam, professionalism has been regulated by referring to prophetic values. Prophetic values ​​are values ​​that exist in the Prophet Muhammad SAW. Prophetic values ​​are the values ​​of professionalism that are directly actualized by the Prophet Muhammad. With these values, he gained a lot of public trust at that time. These values ​​that Indonesian people should implement today in every daily activity and the world of work.